Temperature Dependences of Dynamic Parameters of Water in Fossil-Coal Pores - Alexeev, A.D.; Vasilenko, T.A.; Kirilov, A.K.; Molchanov, O.M.; Troitsky, G.A. (Ukrainian Journal of Physics, 2012)
The results of nuclear magnetic resonance (NMR) studies of water relaxation times, T1 and T2, and self-diffusion coefficients, D, in water-saturated pores of fossil coal (anthracite A) are reported. The spin-echo and broad-line NMR measurement techniques were used. The resonance frequency of 1H spins was found to equal f ≈ 20 MHz in the temperature, T, range from 90 K to room temperature. The results of experiments evidence the existence of a smeared phase transition in the temperature range T = 180–230 K. Using the Uo–Fedin technique, the corresponding phase transition energy was estimated to be U0 = 27–35 kJ/mol. The activation energy Ea associated with the T2(T) dependence was found to increase from 4 kJ/mol at T = 90 K to 18 kJ/mol at T = 300 K. The deviation of the temperature dependence of the self-diffusion coefficient D from the Arrhenius law was explained by the change-over from the bulk diffusion mode to the surface one as the temperature decreased.